LEADERSHIP AND MANAGEMENT DEEP CONFLICT ORGANIZATION - Eko Prabowo; Cecep Castrawijaya (Advances In Social Humanities Research, 2023)
Conflict management is a different matter. Conflicts can occur in leadership or organizations that usually occur, namely differences of opinion or orientation between individuals or groups. All conflict problems can be resolved in various ways and methods. In one leadership, it is likely that there will be many conflicts or misunderstandings that will lead to hostility. In the organization, there are also many conflicts between different opinions of an organization leader and members. This is common in leadership and organization as well as in management. When a conflict arises within an organization, the cause is always identified as poor communication. Likewise, when a bad decision is made, ineffective communication is always the scapegoat. Conflict is not always detrimental but can also be beneficial in the long run. Conflict can change behavior and can make the conflicting parties aware of their mistakes. Awareness of this error will be able to increase productivity.